Preschool Summer Language Program. A Final Report Presented to the Educational Program Committee of North Clackamas School District - Conover, Kathleen D.; Bakke, Sharon K.; North Clackamas School District 12, Milwaukie, OR. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The report examines a summer program for 22 speech and language delayed preschool children. It is explained that a 6 week speech and language program for the children was supplemented by a series of four parent training sessions. Aspects of the child's program, including personnel, transportation, physical setting, scheduling, large group activities, work time activities, and play time activities are described. Positive comments on the program's effects are cited. Among the appended materials, which comprise nearly one half the document, are a list of materials used and sample organizational and individualized educational program forms. (CL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Language Handicaps; Parent Education; Preschool Education; Speech Handicaps; Summer Programs; Reports, Descriptive